Developing as-built BIM model process management system for general contractors: A case study - Lin, Yu-Cheng; Lee, Hsin-Yun; Yang, I-Tung (Journal of Civil Engineering and Management, 2016)
As the application of building information modeling (BIM) becomes more common, BIM model management becomes necessary and important to enhance the effectiveness of BIM implementation for a general contractor (GC) during the construction phase. Implementation of BIM models in the construction phase, which typically involves participants from different fields, often has numerous BIM-related interfaces and problems. Therefore, feedback from the most recent as-built model tracking and BIM model problems are essential for BIM process management (BIM PM) in the construction field. BIM PM has become the most important aspect of a sound as-built BIM model management strategy. Changes in as-built BIM models should be identified, updated, and tracked for BIM PM, such that version management of as-built BIM models can be improved, while minimizing rework and reducing as-built BIM models development duration. Systematic approaches and information on management platforms for enhancing BIM PM during the construction phase are lacking. This study proposes a novel approach to the BIM model management which is to manage and track all versions of as-built BIM models. The primary purpose of this study is to develop a web Construction BIM-based PM (ConBIM-PM) system to enhance a General Contractor’s ability to share BIM PM information and track construction projects more efficiently. The ConBIM-PM system provides users with a centralized storage of all versions of as-built models during the construction phase of a project so that they are able to track and manage the current status of modified as-built models and BIM PM information effectively. Finally, the ConBIM-PM system is applied to a case study of a building project in Taiwan to verify its efficacy and demonstrate its effectiveness. The case study results show that the ConBIM-PM system is effective for BIM PM work by a GC during the construction phase of the BIM implementation.First published online: 24 Aug 2015